2023
DOI: 10.5267/j.uscm.2022.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supply chain risk management on supply chain resilience: The intervening part of Internet-of-Things

Abstract: The aim of this study is to investigate the effect of supply chain risk management on supply chain resilience in the presence of Internet-of-Things as an intermediate variable. In other words, the study seeks to identify whether supply chain risk management completely affects supply chain resilience. Collecting data by a questionnaire from a sample composed of managers of Jordanian industrial firms, the results show that supply chain risk management has a direct and indirect effect on supply chain resilience t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The research also highlights the role of redundancy in building and improving resilience by providing a buffer against the risk of supply chain disruption (Yin & Ran, 2022). Moreover, it is suggested that supply chain resilience can be strengthened through effective management of supply chain risks, including the use of Internet-of-Things and stakeholder engagement (Al-Ayed & Al-Tit, 2023). The importance of supply chain agility in enhancing resilience has been supported by previous research, indicating a positive effect of supply chain agility on supply chain resilience (Pratondo et al, 2021).…”
Section: Supply Chain Resiliencementioning
confidence: 98%
“…The research also highlights the role of redundancy in building and improving resilience by providing a buffer against the risk of supply chain disruption (Yin & Ran, 2022). Moreover, it is suggested that supply chain resilience can be strengthened through effective management of supply chain risks, including the use of Internet-of-Things and stakeholder engagement (Al-Ayed & Al-Tit, 2023). The importance of supply chain agility in enhancing resilience has been supported by previous research, indicating a positive effect of supply chain agility on supply chain resilience (Pratondo et al, 2021).…”
Section: Supply Chain Resiliencementioning
confidence: 98%
“…So, many researchers develop strategies for building resilient, effective, stable, and sustainable SCs using Industry 4.0 technologies including artificial intelligence (AI), the Internet of things (IoT), block chains, and E-supply chains. Firms with these technologies can ensure that they can match up their information processing capabilities with the requirements, and this will lead to improving the SCRM capabilities and boosts supply chain resilience [35][36][37][38].…”
Section: Supply Chain Nervousnessmentioning
confidence: 99%
“…Sebastian and his colleagues mentioned that new technologies-especially social and mobile technologies, analytics, cloud, and internet of things (IoT)-have transformed the way of doing business by changing Possibilities and opportunities and creating threats to Major old Businesses, and those that fail to adopt these technologies and a digital transformation approach are Ready to lose (Sebastian et al, 2017;Al-Ayed & Al-Tit, 2023). Osmundsen et al (2018) tried to find answers to the question of why organizations undergo digital transformation, and they analyzed this effect on organizations.…”
Section: Digital Transformationmentioning
confidence: 99%